Purification and Biochemical Characterization of Polyphenol Oxidase from Alanya Banana (Musa carevendishi) - KARAKUS*, EMINE; PEKYARDIMCI, SULE (Asian Journal of Chemistry, 2010)
Polyphenol oxidase was isolated from Alanya banana (Musa carevendishi) fruit grown in Southern Turkey with ammonium sulfate precipitation and dialysis method. One protein fraction was obtained with gel filtration chromatography. Optimum temperature for banana polyphenol oxidase was 25 °C with catechol substrate. Polyphenol oxidase showed maximum activity at pH 7.0 with catechol, caffeic acid, pyrogallol, 7.2 with 4-methylcatechol, 7.4 with L-tyrosine, 7.8 with p-cresol, 8.0 with gallic acid. Km and Vmax values in the case of 20 mM catechol as substrate were 15.95 mM and 1776 ΔA min-1, respectively. Six different inhibitor were tested in this study and the most effective inhibitors for banana polyphenol oxidase were found to be L-cysteine, β-mercaptoethanol and sodium diethyldithiocarbamate. Inhibition constants (Ki) were calculated for every inhibitor at optimum pH of polyphenol oxidase activity. Polyphenol oxidase isoforms were determined by using the partially purified banana polyphenol oxidase. Polyphenol oxidase isoforms migrated as 4 active bands with catechol substrate, 4 bands with Coomassie Brillant R-250 during native polyacrylamide gel electrophoresis (N-PAGE). On the SDS-PAGE, banana polyphenol oxidase produced 5 bands of ca. 105 kDa, 52 kDa, 26 kDa, 18 kDa and 15 kDa molecular weights. The activation energy, inactivation rate constant and half-lives (t1/2) of polyphenol oxidase were also calculated.